The Binary Fraction of B-type Runaway Stars from LAMOST DR8 - Kun Chen; Yanjun Guo; Dengkai Jiang; Zhanwen Han; Xuefei Chen (The Astrophysical Journal, 2025)
Runaway stars are defined as stars that depart from their birth clusters at high peculiar velocities. There are two main mechanisms for the formation of runaway stars, i.e., the binary-supernova scenario (BSS) and the dynamical ejection scenario (DES). Investigating the binary fraction of runaway stars is an important step in further exploring the relative significance of the two mechanisms. We analyzed the binary fraction of 203 Galactic B-type runaway stars identified in the Large Sky Area Multi-Object Fiber Spectroscopic Telescope Data Release 8 database. Our analysis of radial velocity variations in the runaway star sample reveals an observed spectroscopic binary fraction of 5.4% ± 1.6%, representing the proportion of objects that exhibit statistically significant variations in radial velocity with amplitudes larger than 16 km s ^−1 . We employed a Monte Carlo method to correct for observational biases and determined an intrinsic binary fraction of 27% ± 8%. The period and mass ratio distributions that best reproduce the observation are f ( P ) ∝ P ^−5.7 for 1 ≤ P ≤ 1000 days, and f ( q ) ∝ q ^−3.6 for 0.1 ≤ q ≤ 1.0, indicating a preference for binaries with shorter periods and less massive companions compared to a uniform distribution. The intrinsic binary fraction, in combination with previous studies on the binary fractions of runaway stars formed by the BSS and the DES, implies that both scenarios contribute comparably to the formation of Galactic B-type runaway stars, where the ratio of the BSS to the DES is 0.86.